2021
DOI: 10.1177/00368504211021751
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and genotoxicity in juvenile African catfish, Clarias gariepinus exposed to formulations of glyphosate and paraquat

Abstract: The aquatic ecosystem is under increasing pressure from environmental contaminants due to anthropogenic activities. This study investigated the potential of glyphosate and paraquat to induce DNA damage and other cell abnormalities in juvenile African Catfish, Clarias gariepinus. Juvenile fish were exposed for 96 h to 0.36, 0.48, 0.60, 0.72 and 0.84 mg/L glyphosate; and 0.018, 0.037, 0.055, 0.110 and 0.221 mg/L paraquat. Following the exposure, the fish liver and blood were analysed for DNA damage and micronucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
1
3
0
3
Order By: Relevance
“…Among these organisms, fish are considered bioindicators of aquatic environments, and because they are subject to various toxic compounds, they can ingest or accumulate them through feeding 20 . Recent studies showed that GBH could cause DNA damage, oxidative stress, and hepatotoxicity 21–23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these organisms, fish are considered bioindicators of aquatic environments, and because they are subject to various toxic compounds, they can ingest or accumulate them through feeding 20 . Recent studies showed that GBH could cause DNA damage, oxidative stress, and hepatotoxicity 21–23 …”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies showed that GBH could cause DNA damage, oxidative stress, and hepatotoxicity. [21][22][23] Danio rerio (zebrafish) has a high sensitivity to compounds present in water and can accumulate them in different organs. 24,25 Therefore, it is considered a good model for studies in ecotoxicology, on assessing pollutants levels and endocrine disruptors.…”
mentioning
confidence: 99%
“…In the last few years, exposure studies have been focusing on determining DNA damage since it strongly relates to or even causes all proven problems [ 14 ]. Exposure of the African catfish to glyphosate triggered the formation of micronuclei abnormalities and other nuclear abnormalities such as bean-shaped cells, while the comets formed in the analyses of the liver cells indicated potential genotoxic properties [ 15 ]. Previously, experiments by Koller et al in a buccal epithelial cell line proved that exposure to glyphosate and/or Roundup led to elevated frequencies of micronuclei and nuclear buds and increased membrane damage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A qualidade ambiental atualmente está comprometida pelo aumento da população humana, agricultura intensiva, industrialização e urbanização. A intensidade na exploração dos recursos naturais agravou ainda mais os problemas ambientais (AYANDA et al, 2021). Os agrotóxicos tornaram-se indispensáveis na agricultura moderna para controlar pragas e ervas daninhas a fim de produzir alimentos adequados para a população global, garantir o crescimento de safras, gerar lucro, elevar o padrão de vida humana, proteger as plantações nos campos e alimentos armazenados, além de destruir criadouros de diferentes doenças (ULLAH et al, 2019).…”
Section: Introductionunclassified
“…Desta forma essas atividades antrópicas impactam o ambiente aquático (AYANDA et al, 2021). Paralelamente aos avanços tecnológicos, surge um problema mundial, que é a contaminação de córregos e rios (DAVICO et al, 2020), através da pulverização, escoamento e lixiviação do solo (SHAHJAHAN et al, 2019), que atingem as águas superficiais e subterrâneas, resultando em efeitos diretos ou indiretos nos organismos aquáticos, alvo e não-alvo (ITURBURU et al, 2018).…”
Section: Introductionunclassified